PRAKTIK SUAP VS TRANSFORMASI DIGITAL DALAM PELAYANAN DI LEMBAGA PERADILAN MENUJU GOOD COURT GOVERNANCE - Susiana Setianingsih; Ratna Indriasari; Cornelia Evelin Cabui; Definitif Endrina Kartini Mendrofa; catur widiatmoko (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2025)
Judicial institutions tend to avoid using information technology. The phenomenon of rampant bribery in judicial institutions, which is often used to speed up the process of handling cases, is often the main source of income for court officials. This condition makes some officials reluctant to adopt information technology. This descriptive research aims to find out the reasons behind the rampant practice of bribery - which is included in the category of judicial corruption - amidst the efforts of the Supreme Court, as one of the pinnacles of judicial power, to carry out digital transformation in services for justice seekers. The results show that legal morality is no longer the main guideline for some law enforcers. Monopolistic factors, greed, and protection from certain leadership hinder the optimization of digital transformation as a supporting system for Good Court Governance (GCG). As a result, services to the justice-seeking public have not been maximized. Bribery is clearly contrary to the principles of GCG, while digital transformation is precisely the core element to realize it.